Acute and delayed toxicity from co-ingestion of methylene chloride and methanol. Issue 1 (1st January 2019) - Jaffe, Todd A.; Boyer, Edward W.; Erickson, Timothy B.; Studley, Heather; Hayes, Bryan D.; Chai, Peter R.
Abstract: Methylene chloride is a volatile, chlorinated hydrocarbon and colorless solvent found in multiple industrial products including paint strippers, metal cleaners, automotive products, pesticides and aerosol containers. Occupational exposure to methylene chloride is reported in automotive technicians, painters, and other industrial workers with adverse health effects including gastrointestinal, neurological, as well as hepato-renal injuries. International Agency for Research on Cancer (IARC) classifies methylene chloride as a 2 A carcinogen. Through a series of reactions catalyzed by cytochrome P450 2E1 (CYP2E1), metabolism of methylene chloride leads to the formation of formyl chloride, and ultimately carbon monoxide (CO). Most reports of methylene chloride toxicity are due to dermal and inhalational exposure in occupational settings. Ingestion of methylene chloride is uncommon, yet can lead to significant toxicity and prolonged CO toxicity. Methylene chloride is frequently formulated with methanol; individuals who intentionally ingest methylene chloride can experience concomitant methanol toxicity. We present a case of acute ingestion of paint stripper containing methanol and methylene chloride. We discuss the clinical presentation, key management decisions, relevant pathophysiology and biochemistry, as well as the clinical course and management.